Elaboração do Teste de Reconhecimento de Faces Brasileiro (TRFBr) - Vasconcelos, Aline Miranda de (2018)
Prosopagnosia is a neurocognitive disorder in which individuals do not recognize faces of close people (family and friends) and sometimes not even their own. It is estimated that prevalence of prosopagnosia is approximately 2% of the world population. The most used tests in the evaluation of face recognition (Benton Face Recognition Test and Recognition Memory Test for Faces) have considerable limitations, since it is verified that even people with prosopagnosia, through the use of non-facial information, such as the hairstyle and imperfections in the image, may perform normally in the test. The present study is an experimental, descriptive research with quantitative data approach, aiming to develop a facial recognition test adapted to the Brazilian context (TRFBr). The first step of the study consisted of the elaboration of TRFBr, developed through images taken from a bank of faces of individuals from the Brazilian population (LACOP Facial Expression Database). The second step of the study was the application of the developed test in a sample composed of 102 healthy students of the psychology course, aged 18 to 40 years, voluntarily selected at the Federal University of Paraíba. The sociodemographic questionnaire, Anxiety Scale, Numbers and Letters Test, Boston naming test and the Benton Facial Recognition Test were used for the evaluation. The results of the psychometric analysis showed that TRFBr is a valid and reliable instrument (α= 0,796). Participants had an average of 49,81 (SD = 5,78) scores on TRFBr. Women were more ability in facial recognition tests and older adults performed better than younger participants in Stage A of TRFBr that seeks to evaluate the recognition of the individual with the constancy of angulation and change in emotional expression. The results reveal that TRFBr is a sensitive instrument in analyzing the individual's ability to recognize faces and and can be used in clinical practice and research to assist diagnoses and guide interventions.